Comparison of changes in the dental transverse and sagittal planes between patients treated with self-ligating and with conventional brackets - Javier Moyano; Diana Montagut; Ramon Perera; Javier Fernández-Bozal; Andreu Puigdollers (Dental Press Editora, 2020)
ABSTRACT Introduction: Several advantages have been established regarding the efficiency of self-ligating brackets (SL). In spite of some controversy surrounding this question in the literature, clinical results confirm that "arch development" requires fewer extractions. Objective: The objective of this study was to compare changes in the transverse and sagittal planes in patients treated with conventional ligating brackets (CL)as well as in patients treated with SL brackets and oversized arches. Methods: A sample was selected from a pool of 300 consecutive cases treated by a single clinician: 51 patients with SL brackets and oversized wires, and 55 with CL brackets. These two groups were compared with a control group of 20 patients. All plaster models were scanned and dental landmarks were measured to identify changes from commencement (T0) to conclusion (T1) of treatment. Lateral cephalograms were analyzed for changes in the lower incisor (IMPA) and the first lower molar distal angulation (MAng). Intraoperator reliability was tested with linear regression analysis. To assure all groups were comparable at T0, an ANOVA test with a 95%confidence interval (CI) was performed for all values. To assess changes from T0 to T1 in all groups, a Student's t-test with 95% CI was used. Finally, results from the three groups were compared using an ANOVA-test (95% CI) and a post-hoc test. Results: Increases in all the transverse variables were recorded in the two groups treated (SL and CL), except for the lower intercanine distance in the SL group. IMPA difference from T0 to T1 was higher in the CL group, and molar distal angulation (MAng) took place in the SL group. Conclusions: Self-ligating brackets with oversized arches and conventional ligating brackets showed increases in all variables in the transverse plane, except for the SL group at the mandibular intercanine distance. In comparison with the CL group, fewer different IMPA values were observed in the SL group, in which distal molar angulation occurred.